REFLEKSI KONSEP MITSEIN DAN DAS MAN DALAM INKLUSI SOSIAL DI INDONESIA - Amalia Chairunnisa Rosyid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
Social inclusion has been one of the development goals of Indonesia. Inclusion programs that have been implemented in recent years are based on policies that are formulated in an inclusive manner, but their implementation does not always result in inclusiveness. This study aims to analyze the implementation of social inclusion that has been pursued in Indonesia, by describing the implementations that still encounter challenges and problems. This includes the implementation of policies that are inclusive in nature but tend to be exclusive in their implementation. The discussion of social inclusion and its implementation is then reflected through the concepts of Mitsein and das Man, philosophical ideas of Martin Heidegger. This existential philosophical thinking forms the basis of social philosophy, which views social relations as the essence of human existence. That is, humans always exist together with other humans. The conclusion of this study provides a reflective proposal, in the form of a re-examination of the concepts of Mitsein and das Man in reviewing the implementation of social inclusion in Indonesia.